2022
DOI: 10.3390/nu14030480
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about the Microbiome in Cystic Fibrosis? Is There a Role for Probiotics and Prebiotics?

Abstract: Cystic fibrosis (CF) is a life-shortening genetic disorder that affects the cystic fibrosis transmembrane conductance regulator (CFTR) protein. In the gastrointestinal (GI) tract, CFTR dysfunction results in low intestinal pH, thick and inspissated mucus, a lack of endogenous pancreatic enzymes, and reduced motility. These mechanisms, combined with antibiotic therapies, drive GI inflammation and significant alteration of the GI microbiota (dysbiosis). Dysbiosis and inflammation are key factors in systemic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 273 publications
1
30
0
Order By: Relevance
“…In this case, the random forest predictive model correctly predicted age category of cwCF with 45% error ( Figure 1C) , an error value higher than previously reported for infants without CF 8 . This decrease in prediction accuracy is not surprising, as several studies have shown that there is a marked dysbiosis in the gut of cwCF 1,2,4,6,9,21 . Additionally, Hayden et al showed that cwCF have a delayed maturation of gut microbiota 8 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this case, the random forest predictive model correctly predicted age category of cwCF with 45% error ( Figure 1C) , an error value higher than previously reported for infants without CF 8 . This decrease in prediction accuracy is not surprising, as several studies have shown that there is a marked dysbiosis in the gut of cwCF 1,2,4,6,9,21 . Additionally, Hayden et al showed that cwCF have a delayed maturation of gut microbiota 8 .…”
Section: Resultsmentioning
confidence: 82%
“…These interactions between gut microbiota and the host have been shown to be especially important in the first few years of a child’s life, when communication between immune cells and intestinal microbiota trains the immune system and shapes how cwCF respond to future infections 6,11,14,16,1718 . Individuals with chronic lung diseases, such as asthma, emphysema, and CF have benefited from gut microbiome manipulation: it has previously been shown in both mouse models and clinical trials that manipulating the gut microbiome, whether by probiotics, prebiotics, or fecal microbial transplants, lung disease progression was attenuated 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…A frequent lowering in the abundance of protective bacterial species such as Acinetobacter Iwoffii and Lactobacillus species with a corresponding increase in Bacteriodes fragilis and mycobacterial populations is observed in a CF gut. Alteration in microbial diversity enhances the pro-inflammatory effect associated with CF and dysbiosis and has been implicated in CRC development [ 9 , 11 , 13 ].…”
Section: Role Of Cftr In Normal Physiological Conditions and Its Dysf...mentioning
confidence: 99%
“…Bacterial dysbiosis and associated inflammation is commonly found in the gut of both human patients with CF and in CFTR KO mice [ 13 , 87 , 92 , 93 , 94 , 95 , 96 , 97 ]. The link between CFTR deficiency and microbial dysbiosis is consistent with the key role that intestinal ion transport has on the composition of gut microbiota [ 98 ].…”
Section: Potential Mechanisms By Which Cftr Deficiency Promotes Carci...mentioning
confidence: 99%
“…Even more important is the finding that CF patients themselves had dysbiosis and that this could explain at least in part not only the intestinal disorders but also the respiratory ones. The acquisition of previously unknown information about the importance of some bacteria, i.e., those partially or totally disappeared in the gut of CF patients, in the regulation of the activity and function of both the gut and the lung was the base to suggest the use of these microorganisms, the so-called probiotics, in CF patients [ 18 , 19 ]. Main aim of this paper is to discuss which are the biological basis for probiotic administration to CF patients and which results could be expected.…”
Section: Introductionmentioning
confidence: 99%